On closed-form solutions of triple series equations involving Laguerre polynomials - Dhaliwal, R.S.; Rokne, J.; Singh, B. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We consider some triple series equations involving generalized Laguerre polynomials. These equations are reduced to triple integral equations for Bessel functions. The closed-form solutions of the triple integral equations for Bessel functions are obtained and, finally, we get the closed-form solutions of triple series equations for Laguerre polynomials.